ANALISA DESAIN BERDASARKAN TEORI âTHE ESSENTIAL OF DESIGNâ KENDALL PADA SISTEM INFORMASI PERPUSTAKAAN DIGITAL STMIK PPKIA PRADNYA PARAMITA MALANG - Husni, Mochamad; Ihsan, SaÃ¢Â€Â™atul (DINAMIKA DOTCOM, 2012)
Design user interface and data entry procedure STMIK Digital Library Information Systems PPKIA Pradnya Paramita Malang is still not meet the rule of making a good design so that the user interface and data entry procedure can not execute their respective functions resulting digital library is not able to function as sources of information and the science as well as journals or publications of scientific articles in digital format. The theory of "The Essential of Design" Kendall is a theory that contains the rules and principles in making a web design, including the user interface design which includes layout rules, standards and consistency of operation, limits the choice menu, using natural language and include guidelines on dialog design and data entry procedure which includes about coding or command on the button or link that is able to effectively bring users to the desired condition.Key words: Kendall, "The Essential of Design", the data entry procedure, user interface, web design, digital libraries.